The validity of self-reported antiretroviral use in persons living with HIV: a population-based study - Grabowski, M.K.; Reynolds, S.J.; Kagaayi, J.; Gray, R.H.; Clarke, W.; Chang, L.C.; Nakigozi, G.; Laeyendecker, O.; Redd, A.D.; Goud-Billoux, V.; Ssekubugu, R.; Nalugoda, F.; et al. (AIDS, 2018)
To assess the validity of self-reported antiretroviral therapy use (ART) using population-based cohort data. Methods—Self-reported ART use and non-use was compared to a validated laboratory assay in 557 HIV-positive participants in the Rakai Community Cohort Study surveyed between September and December 2011 in Rakai, Uganda. The study population included participants from seven communities, including one fishing community with high HIV prevalence (~41%). ART use was assayed using liquid chromatography-tandem mass spectrometry which detects 20 antiretroviral (ARV) drugs. HIV viral load measurements were also obtained. Individuals with ≥2 antiretroviral (ARV) drugs detected were considered to be using ART. Results—153 (27%) participants self-reported ART use of whom 148 (97%) had ≥2 ARV drugs detected. There were ≥2 ARV drugs detected in 11% (n=44/404) of individuals with no self-reported ART use. Overall, the specificity of self-reported ART use was 99% (95%CI:97–100%) and the sensitivity was 77% (70–83%). Positive and negative predictive values were 97% (95%CI: 93–99%) and 89% (95%CI: 86–92%), respectively. Non-disclosure of ART use was significantly more common in younger persons (<30 years) and among those in trading occupations, but did not vary by community of residence. Conclusions—Self-reported ART use has high specificity and moderate sensitivity providing reasonable, but conservative estimates of population-based ART use. There is more under- reporting of ART use among younger persons and traders suggesting a need for more research on barriers to self-reporting of ART use in these sub-groups.
Keywords: AIDS; HIV; Antiretroviral therapy; Combination HIV prevention; Self-report; Validity; Uganda; Sub-Saharan Africa